68 The prognostic and predictive implications of the 12-chemokine score in muslce invasive bladder cancer. (10th December 2020) - Li, Roger; Zemp, Logan; Berglund, Anders; Dhillon, Jasreman; Putney, Ryan; Kim, Youngchul; Jain, Rohit; Grass, Daniel; Zhang, Jingsong; Poch, Michael; Pow-Sang, Julio; Sexton, Wade; et al.
Abstract : Background: Emerging evidence from studies in sarcoma and melanoma immune checkpoint blockade(ICB) trials demonstrated enhanced efficacy in tumors harbouring tertiary lymphoid structures(TLS) 1–3 - lymph node like aggregates in the tumor microenvironment postulated to recruit lymphocyte infiltration and coordinate tumor antigen presentation and lymphocyte priming. Previously, our group described a 12-chemokine metagene signature that reflects strong intratumoral chemotactic signalling and accurately predicts the presence of TLS in colorectal carcinoma. 4 Grounded in these works, we attempted to correlate high 12CK signature with TLS formation in the context of muscle invasive bladder cancer(MIBC), and then sought to define its prognostic implications and its ability to predict response to ICB. Methods: A total of 130 MIBC samples were arrayed on Affymetrix microarrays and 12CK scores were assessed. Scores were normalized using 12CK>1 to denote 12CK-High(n=24). We then investigated the the presence of TLS with the associated immune cellular infiltration evaluated by immunohistochemistry and gene signature deconvolution method (xCell). 5 12CK scores were also correlated with survival in our institutional cohort and validated using data from TCGA. Finally, 12CK scores were extracted from the IMVIGOR210 study to examine its ability to predict response to ICB. 6 Results: Type III TLS, consisting of germinal center-like structures and discrete T-cell zones were found in 7/22 12CK-High vs. 0/21 12CK-Low tumors (p=0.009) (figure 1 a). Additionally, a more robust immuno-environment was seen in 12CK-High tumors, consisting of increased infiltration of CD4+ T lymphocytes (p=0.1), CD8+ T lymphocytes (p=0.02), activated dendritic cells (p=0.047), and B lymphocytes (p=0.006) on immunohistochemistry (figure 1 b). Furthermore, on xCell deconvolution, M1 macrophage, NK cells, CD8+ Tem, CD4+ Tem, and memory B cells were enriched in 12CK-High tumors, suggesting both a heightened innate and adaptive immune response (figure 1 c, d). Kaplan-Meier survival analyses of our internal cohort revealed improved PFS (HR 0.25, p=0.003 ), CSS (HR 0.25, p=0.003), and OS (HR 0.55, p=0.03) amongst 12CK-High patients (figure 2 a-c). From the TCGA, similar improvements were found in PFS (HR 0.55, p=0.007), CSS (HR 0.40, p=0.002), and OS (HR 0.59, p=0.01) in 12CK-High patients (figure 2 d-f). From the IMVIGOR 210 study, complete responders exhibited significantly higher 12-CK scores than all other groups (figure 2 g). Strikingly, the 12CK-High signature conferred a median overall survival benefit of almost 1 year in the atezolizumab-treated patients (figure 2 h). Conclusions: In muslce invasive bladder cancer, 12CK-High scores corresponded with formation of TLS in the TME; favourable prognosis in surgically treated MIBC patients; and CR in atezolizumab-treated patients. References: Cabrita R, Lauss M, Sanna A, et al. Tertiary lymphoid structures improve immunotherapy and survival in melanoma. Nature 2020;577(7791):561–565. Helmink BA, Reddy SM, Gao J, et al. B cells and tertiary lymphoid structures promote immunotherapy response. Nature 2020;577(7791):549–555. Petitprez F, de Reyniès A, Keung EZ, et al. B cells are associated with survival and immunotherapy response in sarcoma. Nature 2020;577(7791):556–560. Aran D, Hu Z, Butte AJ. xCell: digitally portraying the tissue cellular heterogeneity landscape. Genome biology 2017;18(1):220. Rosenberg JE, Hoffman-Censits J, Powles T, et al. Atezolizumab in patients with locally advanced and metastatic urothelial carcinoma who have progressed following treatment with platinum-based chemotherapy: a single-arm, multicentre, phase 2 trial. Lancet (London, England). 2016;387(10031):1909–1920.